TrkB-expressing paraventricular hypothalamic neurons suppress appetite through multiple neurocircuits - Juan Ji An (Nature Portfolio, 2020)
The TrkB receptor is known to regulate obesity via appetite control, but the underlying neural circuits are not known. Here, the authors show that selective modulation of TrkB+ neurons in the paraventricular hypothalamus regulates food intake via circuits to ventromedial hypothalamus and lateral parabrachial nucleus.